The Role of Decorin and Biglycan Signaling in Tumorigenesis - Diehl, Valentina; Huber, Lisa Sophie; Trebicka, Jonel; Wygrecka, Malgorzata; Iozzo, Renato V.; Schaefer, Liliana (Frontiers in Oncology, 2021)
The complex and adaptive nature of malignant neoplasm constitutes a major challenge for the development of effective anti-oncogenic therapies. Emerging evidence has uncovered the pivotal functions exerted by the small leucine-rich proteoglycans, decorin and biglycan, in affecting tumor growth and progression. In their soluble forms, decorin and biglycan act as powerful signaling molecules. By receptor-mediated signal transduction, both proteoglycans modulate key processes vital for tumor initiation and progression, such as autophagy, inflammation, cell-cycle, apoptosis and angiogenesis. In spite of their structural homology, these two proteoglycans interact with distinct cell surface receptors and thus modulate distinct signaling pathways that ultimately affect cancer development. In this review, we summarize growing evidence for the complex roles of decorin and biglycan signaling in tumor biology and address potential novel therapeutic implications.